Perceptual analysis of women on tubectomy and other family planning services: a qualitative study - Kalra, Ruchi; Phadnis, Sameer; Joshi, Ankur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In our country India, Population explosion has become a major concern to all. As per NHFS 3 report, in MP 44.3%, adopted the female sterilization other methods like male sterilization 1.3%, Intrauterine devices 0.7% and pills users were 1.7%, condom 4.8%. The study probed into the reasons of female sterilization as the method of choice and to know ideas of other temporary contraceptives and male sterilization. Methods: In the study qualitative technique was adopted to understand the perception of participants. FGD’s and in-depth interviews were conducted with residents of Ratua village between Nov 2011 - April 2012 to explore the gaps. 52 women participated in the study. They were between 20-40 years, married and had children. Results: The interview transcripts were thematically analysed. All the participants knew tubectomy operation either through health care workers, friends, relatives or media. They thought it as a better and safer way to prevent unwanted pregnancy as compared to temporary ways and male sterilization. Economic incentives were looked up as insufficient motivation for undergoing the procedure. The decision was combined and women had less freedom in decision making. All felt strongly need of having at least one son for the family progression and care provider to them during the old age. They were hesitant to use temporary methods as they had misconceptions about the adverse effects. The male sterilization was unacceptable to all the participant as they thought it causes weakness and would adversely affect the physical work performance of their husband Conclusions: Participants in the study were hesitant to use temporary contraceptive methods for the fear of adverse effects. Multiple approaches to educate and transform their misconceptions of contraceptive methods and male sterilization should be adopted.